2014
DOI: 10.1007/s00540-014-1819-5
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of [Met5]enkephalin-induced antinociception by mixture of three peptidase inhibitors in rat

Abstract: The present data, together with those of earlier studies, clearly demonstrate that amastatin-, captopril-, and phosphoramidon-sensitive enzymes play an important role in inactivation of opioid peptides at the spinal level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A previous study demonstrated that pretreatment with i.t. administration of a combination of 10 nmol each of amastatin (A), captopril (C) and phosphoramidon (P) completely inhibited peptidase-induced degradation of ME (Murata et al, 2014). In the present study, i.t.…”
Section: Combination Of Me and Sialorphin Together With Acpsupporting
confidence: 52%
See 4 more Smart Citations
“…A previous study demonstrated that pretreatment with i.t. administration of a combination of 10 nmol each of amastatin (A), captopril (C) and phosphoramidon (P) completely inhibited peptidase-induced degradation of ME (Murata et al, 2014). In the present study, i.t.…”
Section: Combination Of Me and Sialorphin Together With Acpsupporting
confidence: 52%
“…accordance with the method in earlier studies by the present group (Kitamura et al, 2000;Takahashi et al, 2007;Akahori et al, 2008;Murata et al, 2014;Ajimi et al, 2015;Matsuda et al, 2017), nociceptive stimulation was achieved by immersing the tail of each rat in hot water (55ºC) for a maximum of 5 sec. This time limit was set to prevent injury to the animal in accordance with the result from earlier studies by the present group showing that persistent pain occurs when the tail is placed in hot water for more than 5 seconds (data not shown).…”
Section: Downloaded Frommentioning
confidence: 99%
See 3 more Smart Citations